2004
DOI: 10.1177/0310057x0403200402
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procalcitonin and C-reactive Protein as Markers of Sepsis and Outcome in Patients with Neurotrauma and Subarachnoid Haemorrhage

Abstract: This prospective study evaluated serum procalcitonin (PCT) and C-reactive protein (CRP) as markers for systemic inflammatory response syndrome (SIRS)/sepsis and mortality in patients with traumatic brain injury and subarachnoid haemorrhage. Sixty-two patients were followed for 7 days. Serum PCT and CRP were measured on days 0, 1, 4, 5, 6 and 7. Seventy-seven per cent of patients with traumatic brain injury and 83% with subarachnoid haemorrhage developed SIRS or sepsis (P=0.75). Baseline PCT and CRP were elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 26 publications
3
29
2
Order By: Relevance
“…Our results are in agreement with a study by O'Connor E et al in 2004 [20] that evaluated PCT and CRP as mortality markers in 62 patients with TBI and subarachnoid haemorrhage and they found that serum PCT appeared to correlate with TBI severity and mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with a study by O'Connor E et al in 2004 [20] that evaluated PCT and CRP as mortality markers in 62 patients with TBI and subarachnoid haemorrhage and they found that serum PCT appeared to correlate with TBI severity and mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Serum CRP values reflect the acute phase protein response to injury stimuli and have been shown to correlate well with injury severity [17]. Metabolic stress response analysis using CRP has been shown to be valuable in stratifying the magnitude and duration of injury and in predicting outcome after injury in a variety of patient populations [18][19][20][21]. A recent prospective study of children with acute appendicitis showed improved sensitivity and specificity of serum CRP levels in contrast to WCC when diagnosing appendiceal perforation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the prevalence of SIRS following SAH [6][7][8]12,206,207]. In a series of 207 SAH patients, SIRS or sepsis were identified as the primary cause of death in 67 patients (32.6%).…”
Section: Systemic Inflammatory Responsementioning
confidence: 99%